Agent-based Problem Solving Methods in Big Data Environment - ZHANG, Hao Lan (Institutional Knowledge at Singapore Management University, 2014)
This special issue particularly focuses on using agent-based methods to solve the complex computational problems arising in Big Data environments. It covers the recent advances in the areas of distributed problem solving, agent-based data mining, as well as recommendation systems, working with data extracted from both physical and online environments.